Experimental construction of hunter-gatherer residential features, mobility, and the costs of occupying "persistent places". (March 2018) - Morgan, Christopher; Webb, Dallin; Sprengeler, Kari; Black, Marielle (Pedro); George, Nicole
Abstract: Temporal and caloric costs associated with building common hunter-gatherer residential features – housefloors, housepits, storage pits, rock rings, and various types of wickiups – are presented based on experimental construction of these types of features. For subsurface features, excavation rates and associated labor costs are consistent regardless of feature type, soil type, or feature size. Labor costs for surface features are largely dependent on feature size, complexity, and availability of raw materials. In total, the per-family costs of building a single-family hunter-gatherer residential base are just under one 8-h day and approximately 2500 kcal per person. Combined, these data indicate relatively low costs are associated with hunter-gatherer investments in persistent places and in residential facilities made from locally-available resources. Implied by the study is that initial use of a place might reduce the costs of and thus encourage subsequent reoccupations and that raw material availability may have played as much of a role in decisions about when to move as density and distribution of subsistence resources. Highlights: Common hunter-gatherer residential features were constructed. Construction costs dependent on feature size, complexity, and availability of raw materials. Single–family residential bases built in less than a day and 2500 kcal per person. Initial occupations could reduce costs of some subsequent occupations. Raw material availability implicated in decisions to move.